2018
DOI: 10.1007/s11325-018-1623-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sleep-disordered breathing with ambulatory Holter monitoring

Abstract: Holter-derived respiration detected OSA comparable to PSG. Further study is warranted to determine its utility for screening and diagnosing OSA in appropriately selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Traditionally, electrodes are attached to the torso and connected to a monitor. Among the manuscripts included in this review, the number of electrodes varied between 3 and 12, and the devices could be portable [ 74 , 75 ]. Heart rate data can also be extracted from smart watches [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, electrodes are attached to the torso and connected to a monitor. Among the manuscripts included in this review, the number of electrodes varied between 3 and 12, and the devices could be portable [ 74 , 75 ]. Heart rate data can also be extracted from smart watches [ 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indices derived from ECG signals correlated with self-rated pain among patients taking physical therapy after surgery [ 74 ] and sleep apnea among people with suspected sleep disordered breathing measured by standard PSG [ 75 ]. When ECG indications of pain differed from observation, a recent study with patients under palliative sedation favored the ECG measurement and concluded that it was more objective [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…10,38 More recently, this algorithm was compared by Grasso and colleagues to Polysomnography in a prospective cohort of patients being screened for obstructive sleep apnea. 39 The algorithm derives CSRPB episodes from continuously acquired ECG data by examining beat to beat changes in the QRS complex that occur when the heart shifts in the thorax during inhalation and are associated with an increase in tidal volume. The ECG algorithm computes mean square QRS amplitude variations in 15 second intervals (area divided by width in ¼ microvolts) and derives a mean QRS amplitude waveform at a rate of one sample per second, which is then used to measure changes in tidal volume and calculate CSRPB.…”
Section: Ecg Derived Cheyne-stokes and Periodic Breathing Analysismentioning
confidence: 99%